2020
DOI: 10.1016/j.jfca.2019.103405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sodium levels of processed foods among the International Food and Beverage Association member companies in Australia: 2013–2017

Abstract: Excess dietary sodium is a modifiable cause of high blood pressure. The World Health Organization has targeted a 30% reduction in mean population sodium consumption by 2025.In 2008, members of the International Food and Beverage Alliance (IFBA) made commitments to lower sodium content in their products. The aim of this study was to determine the difference in sodium levels between 2013 and 2017 in foods and beverages produced by companies that are IFBA members (n=10) and non-IFBA members (n=6) that were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The small changes in nutrient compositions seen may align with product reformulation within this retail market [ 41 , 42 , 43 , 44 ], as snacks were seen to have lower median sodium, sugar, and carbohydrate levels at T3 as compared to T2, with sugar increasing at T4. Global research over various time periods reports toddler foods to be high in sugar and/or sodium [ 45 , 46 , 47 , 48 , 49 ]. In addition, an Australian study reported that from 2009–2011, 67% of child-oriented food products underwent reformulation, with 15% having simultaneous positive (e.g., reduction in sodium) and negative (e.g., increase in sugar) reformulations, and overall little improvement in healthiness.…”
Section: Discussionmentioning
confidence: 99%
“…The small changes in nutrient compositions seen may align with product reformulation within this retail market [ 41 , 42 , 43 , 44 ], as snacks were seen to have lower median sodium, sugar, and carbohydrate levels at T3 as compared to T2, with sugar increasing at T4. Global research over various time periods reports toddler foods to be high in sugar and/or sodium [ 45 , 46 , 47 , 48 , 49 ]. In addition, an Australian study reported that from 2009–2011, 67% of child-oriented food products underwent reformulation, with 15% having simultaneous positive (e.g., reduction in sodium) and negative (e.g., increase in sugar) reformulations, and overall little improvement in healthiness.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed: In accordance with our study question, we established a search equation that was used in the different databases and in the following steps: intake, particularly in low-and middle-income countries where the risk of death from high blood pressure is higher, more than double that in high-income countries [66]. Likewise, the WHO encourages the use of tools such as SHAKE to technically assist countries in their fight [67,68].…”
Section: Syntaxmentioning
confidence: 99%
“…Studies on dietary salt/sodium and potassium levels are hard to carry out since they require both resources and appropriate technologies. Beside, the dietary issue remains a challenge in a context whereby the choice of food is individual and varies according to the consumers' tastes [66]. Seven studies were able to assess the sodium level in the staple food.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Так, в Канаде не удалось достичь снижения количества соли в почти половине запланированных продуктов [17]. О недостаточных темпах снижения количества соли в готовых продуктах говорят и австралийские исследователи [34]. Трудности в реализации снижения количества соли в запланированных 150 категориях продуктов испытывают и в США [35].…”
Section: вовлечение производителей пищевой промышленностиunclassified